Bone Mineral Density Status in 48 Iraqi Hyperthyroid Patients - Jassim, Nizar A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Bone disease of hyperthyroidism is a type of high-turnover osteoporosis. In many patientswith hyperthyroidism, there is excessive bone resorption, occasionally marked in degree and farexceeding that in the usual patient with osteoporosis. The purpose of this study was to evaluate the bonemineral density (BMD) in hyperthyroid patients in a controlled study.Patients and Methods. The study group consists of 48 patients with hyperthyroidism who were seen atSpecialized Centre for Endocrinology and Diabetes, and at Rheumatology Clinic and Osteoporosis Clinicin Baghdad Teaching Hospital. In all patients, measurement of BMD at the lumbar spine (L1-L4) usingdual-energy x-ray absorptiometry (DXA) machine was done.Results: The BMD was reduced in 40 patients (83.33%). Seventeen postmenopausal women, 2premenopausal, and 2 men have osteopenia. Fourteen postmenopausal women and 2 premenopausalwomen have osteoporosis. Osteoporosis was not reported in men.Conclusion: When compared with control group, the prevalence of osteopenia in hyperthyroid patientswas statistically significant in postmenopausal women only (p = 0.013).